Multi-Objective Genetic Algorithm Based Coordinated Second- and Third-Order Harmonic Voltage Injection in Modular Multilevel Converter - Lin, Lei; Li, Ang; Xu, Chen; Wang, Yifan (IEEE access, 2020)
The submodule (SM) capacitor voltage ripple and the root mean square (RMS) of the arm current are related to the costs and losses of the modular multilevel converter (MMC). The optimization issues have received great attention. The second-order circulating current control and third-order harmonic voltage injection are two conventional optimization methods, but the existing research neglects their coupling effects. In this paper, these two methods are comprehensively investigated and coordinately combined. First, the various performances of MMC under multiple injections are characterized. Then, a multi-objective optimization model considering the output capability of arm voltage and the energy balance of capacitors, is proposed to reduce the SM capacitor voltage ripple and the RMS of the arm current. The amplitudes and phases of the injected second- and third-order harmonic voltages are designed coordinately by genetic algorithm. The simulation and experimental results have validated the effectiveness and feasibility of the proposed method.